How Big is the Tax Advantage to Debt?: Discussion - Masulis, Ronald W. (Journal of Finance, 1984)
Ronald W. Masulis, How Big is the Tax Advantage to Debt?: Discussion, The Journal of Finance, Vol. 39, No. 3, Papers and Proceedings, Forty-Second Annual Meeting, American Finance Association, San Francisco, CA, December 28-30, 1983 (Jul., 1984), pp. 853-855